Basal Cell Carcinoma Risk Factors: A Case-Control Study from Dr. Hasan Sadikin Hospital of Bandung, Indonesia - Rulandani, Redi; Azhar, Raden Yohana; Putri, Almahitta Cintami (http://dharmais.co.id/, 2025)
Background: Basal Cell Carcinoma (BCC) is the most common non-melanoma skin cancer in humans (75%). BCC is a slow-growing, malignant tumor with a destructive nature, yet it rarely metastasizes. Prevention is better than curative medicine. The risk factors of BCC in Bandung area are still not known. Hence, a study regarding BCC risk factors in Bandung is needed. The objective in this paper is to determine basal cell carcinoma risk factors in Dr. Hasan Sadikin Hospital, Bandung, Indonesia.Method: Analytical research with a case-control approach was carried out on patients with a diagnosis of BCC who came to Dr. Hasan Sadikin Hospital outpatient clinic in Bandung between July and December 2023. Data was collected and analyzed with SPSS version 29.0 using the chi-square method to determine the association between risk factors and BCC occurrence. Risk factors studied in this research were age, gender, occupation, family history, Fitzpatrick skin phototype, duration of sun exposure, time of sun exposure, smoking, alcohol, and chemical exposure.Results: There were 41 subjects in the case group and 82 subjects in the control group. The results of bivariate analysis using chi-square showed that old age (p 0.001; OR (95% CI = 6.35 (2.51–16.04)), duration of sun exposure 8–40 hours within a week (p = 0.049; OR (95% CI) = 2.09 (0.98–4.49)), and sun exposure time from 06.00 to 18.00 (morning to evening) (p = 0.026; OR (95% CI) = 7.25 (2.07–25.41) had significant association with the occurrence of breast cancer. Conclusion: The study conducted at Dr. Hasan Sadikin Hospital, Bandung, found that significant risk factors associated with Basal Cell Carcinoma (BCC) are advanced age, sun exposure duration of 8 to 40 hours per week, and sun exposure during the hours of 06:00 to 18:00 (morning to evening). These findings emphasize the importance of preventive measures by limiting sun exposure, especially among the older population, to reduce the risk of BCC in the Bandung area.